An exploration of primary school students' perceived learning practices and associated self-efficacies regarding mobile-assisted seamless science learning. Issue 18 (12th December 2019) - Lin, Xiao-Fan; Tang, Dandan; Lin, Xuanjun; Liang, Zhong-Mei; Tsai, Chin-Chung
ABSTRACT: This study aimed to explore the relationships between students' perceived learning practices and associated self-efficacies regarding mobile-assisted seamless science learning. The learning practices for mobile-assisted seamless science learning questionnaire was developed with three scales that denote learning supported by mobile technology. These scales included authentic learning, self-directed learning, and collaborative learning with information and communication technology. Associated self-efficacies promoted by mobile-assisted seamless science learning could include authentic problem-solving, creative thinking and academic self-efficacy. A sample of 312 primary school students from China responded to the mobile-assisted seamless science learning questionnaire. Confirmatory factor analyses indicated that the mobile-assisted seamless science learning questionnaire had high reliability and validity. The path analysis results analysed via a structural equation modelling technique implied that primary school students' perceived self-directed learning and authentic learning were important as positive predictors for authentic problem-solving efficacy, which may function as a partial mediation variable in the effect of students' perceptions of learning practices on the academic self-efficacy of mobile-assisted seamless science learning. The findings highlighted that learning practices (i.e. authentic learning and self-directed learning) and authentic problem-solving efficacy are both indispensable and mutually reinforcing. This can provide some insights for promoting mobile learning in science learning in the future.